2022
DOI: 10.1021/acs.jafc.2c02474
|View full text |Cite
|
Sign up to set email alerts
|

miR-455-3p Is Negatively Regulated by Myostatin in Skeletal Muscle and Promotes Myoblast Differentiation

Abstract: Myostatin (MSTN) is a growth and differentiation factor that regulates proliferation and differentiation of myoblasts, which in turn controls skeletal muscle growth. It may regulate myoblast differentiation by influencing miRNA expression, and the present study aimed to clarify its precise mechanism of action. Here, we found that MSTN −/− pigs showed an overgrowth of skeletal muscle and upregulated miR-455-3p level. Intervention of MSTN expression using siMSTN in C2C12 myoblasts also showed that siMSTN signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…MiR-455-3p can improve lipid metabolism in the liver by inhibiting the suppressor of cytokine signalling 3 through SREBP-1c 25 , 26 . Han et al confirmed that the GATA3/miR-455-3p/ Smad2 cascade is involved in regulating muscle development in C2C12 myoblasts 27 . MiR-455-3p inhibited the activation of hepatic stellate cells by targeting the Hsp47/TGF-beta/Smad4 signalling pathway and was recommended as a promising therapeutic target for liver fibrosis 28 .…”
Section: Discussionmentioning
confidence: 97%
“…MiR-455-3p can improve lipid metabolism in the liver by inhibiting the suppressor of cytokine signalling 3 through SREBP-1c 25 , 26 . Han et al confirmed that the GATA3/miR-455-3p/ Smad2 cascade is involved in regulating muscle development in C2C12 myoblasts 27 . MiR-455-3p inhibited the activation of hepatic stellate cells by targeting the Hsp47/TGF-beta/Smad4 signalling pathway and was recommended as a promising therapeutic target for liver fibrosis 28 .…”
Section: Discussionmentioning
confidence: 97%
“…One of these MSTN -edited models, its progeny, or its crosses were further investigated . These include investigations on fiber-type distribution and expression of myosin heavy chain isoforms; shift from slow- to fast-twitch muscle fibers in skeletal muscle; internal organ size; semen quality and fertilization ability; reproductive trait characterization in MSTN -edited crosses; collagen-related pathological features (umbilical hernia and tippy toe standing); regulation of body fat deposition; fibrinogen levels and fibrin clot structure; esophageal striated muscle development and regulation of muscle fiber types; extraocular muscles; cardiac extracellular matrix; growth of smooth muscle in uterine horns of MSTN mutant gilts; smooth muscle content in corpus cavernosum of MSTN mutant boars; erythrocyte osmotic fragility, hematological parameters, and fatty acid composition of serum and erythrocyte membranes; miR-455-3p regulation of myoblast differentiation; composition and alteration of gut microbiota; analysis of meat and fatty acids characteristics; and development of a restriction enzyme-mediated PCR-RFLP assay for genotyping MSTN mutant pigs …”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%
“…They also play a regulatory role in self-renewal and cell proliferation. Moreover, the MYH3 gene can affect muscle fiber type composition and intramuscular fat content in pigs [ 24 , 25 ], and myostatin ( MSTN ) can negatively regulate skeletal muscle growth and development through autocrine or paracrine signaling [ 13 , 26 ]. In addition, skeletal muscle development is associated with epigenetic regulatory mechanisms [ 27 ].…”
Section: Introductionmentioning
confidence: 99%